2017
DOI: 10.2500/ajra.2017.31.4402
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery for Chronic Rhinosinusitis with Nasal Polyps: Clinical Outcome and Predictive Factors of Recurrence

Abstract: ESS proved to be an effective treatment in CRSwNP but with a considerable rate of recurrence. These results indicated an important correlation of occupational dust exposure and non-IgE-mediated asthma with disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 34 publications
(53 reference statements)
7
57
0
8
Order By: Relevance
“…Endoscopic sinus surgery (ESS) is the mainstay treatment for CRS that is refractory to medical therapy. Nevertheless, there is still a 31% to 55% recurrence rate after ESS . Furthermore, it is challenging for physicians to predict surgery outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic sinus surgery (ESS) is the mainstay treatment for CRS that is refractory to medical therapy. Nevertheless, there is still a 31% to 55% recurrence rate after ESS . Furthermore, it is challenging for physicians to predict surgery outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is still a 31% to 55% recurrence rate after ESS. [5][6][7] Furthermore, it is challenging for physicians to predict surgery outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lou and colleagues suggested that a tissue eosinophil proportion of >27% of total cells or a tissue eosinophil absolute count of >55 eosinophils per high‐power field may be reliable as markers for nasal polyp recurrence within 2 years after sinus surgery, whereas Younis and colleagues suggested that the presence of eosinophilic mucin was a strong predictor of CRS recurrence . Similarly, other studies suggested CRSwNP recurrence to be associated with occupational dust exposure, serum periostin, and polypoid change of anterior free border of middle turbinate . However, use of these markers is limited because they are either invasive or impossible to obtain before surgery.…”
mentioning
confidence: 99%
“…Disease recurrence occurred in 31% of the patient, but only 7% required surgical reintervention. Their analysis identified occupational dust 41 exposure and non-immunoglobulin E mediated asthma as independent predictive variables in CRSwNP recurrence (57).…”
Section: Efficacy Of Muv/vis In the Prevention Of Recurrence Of Nasalmentioning
confidence: 99%